References Values of Soluble α-Klotho Serum Levels Using an Enzyme-Linked Immunosorbent Assay in Healthy Adults Aged 18–85 Years - Espuch-Oliver, Andrea; Vázquez-Lorente, Héctor; Jurado-Fasoli, Lucas; de Haro-Muñoz, Tomás; Díaz-Alberola, Irene; López-Velez, María del Señor; de Haro-Romero, Teresa; Castillo, Manuel J.; Amaro-Gahete, Francisco J. (Journal of clinical medicine, 2022)
α-Klotho protein is a powerful predictor of the aging process and lifespan. Although lowered circulating soluble α-Klotho levels have been observed in aged non-healthy individuals, no specific reference values across a wide range of ages and sex using an enzyme-linked immunosorbent assay (ELISA) are available for larger cohorts of healthy individuals. The present analytical cross-sectional study was aimed to establish the reference values of soluble α-Klotho serum levels in healthy adults by age and sex groups. A total of 346 (59% women) healthy individuals aged from 18 to 85 years were recruited. Subjects were divided by sex and age as: (i) young (18–34.9 years), (ii) middle-aged (35–54.9 years), and (iii) senior (55–85 years) individuals. The soluble α-Klotho levels were measured in serum using ELISA. Senior adults were the age-group that presented the lowest soluble α-Klotho serum levels (p < 0.01), with age showing a negative association with soluble α-Klotho serum levels (p < 0.001). No differences between sexes were observed. Therefore, soluble α-Klotho levels were especially decreased—regardless of sex—in our cohort of healthy individuals because of the physiological decline derived from the aging process. We recommend routine assessments of soluble α-Klotho levels using ELISA as a simple and cheap detectable marker of aging that improves quality of life in the elderly.